Metallic pigments for metal watchbands and process for their preparation
Patent Information
- Application Number
- CN202611317527.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-28
- Publication Date
- 2026-10-16
AI Technical Summary
该种全表面处理思路,往往需要形成较为连续甚至较厚的膜层,容易对片状金属颜料大面区域的镜面反射性能造成影响,从而导致金属感减弱、亮度下降或外观发闷
1.本发明通过在片状金属基体边缘区域构筑复合保护环层、在大面区域形成超薄调节层,实现了边缘区域与大面区域的差异化功能分配。由于片状金属基体的边缘区域通常具有更高的表面活性和更易成为介质侵入及失效起始的位置,本发明利用金属转化结合单元与有机硅网状单元在该区域原位复合形成连续分布的复合保护环层,可在边缘部位构建更为稳定的界面结合与阻隔结构,从而有效提高对水分、氧及腐蚀性介质的阻隔能力,增强金属颜料的耐水性、耐腐蚀性及界面稳定性。同时,大面区域仅形成超薄调节层,能够在保证表面调控效果的前提下,尽可能减小膜层对片状金属基体镜面反射性能的不利影响,有利于保持其原有的金属光泽、亮度及装饰效果。此外,复合保护环层沿外缘连续分布并向大面区域呈递减式过渡,形成厚度梯度结构,有助于缓和边缘区域与大面区域之间的界面突变,降低膜层局部应力集中和缺陷产生的可能性,进一步提高膜层结合牢度和结构稳定性。相应地,通过预处理、差异活化、受限水解沉积及分阶段固化相配合的制备过程,能够使复合膜层优先在边缘区域定向构筑并实现稳定成膜,从而使本发明在兼顾防护性能与光学性能保持方面具有更为突出的综合技术优势。
Smart Images

Figure CN122917599A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of metal pigment preparation technology, specifically to a metal pigment for metal watch straps and its preparation process. Background Technology
[0002] Metallic pigments are widely used in coatings, inks, plastics, and surface decoration materials due to their excellent metallic luster, shimmering effect, and decorative properties. Among them, flake-shaped metallic pigments, such as aluminum flakes, aluminum-magnesium alloy flakes, and vacuum-deposited aluminum flakes, are particularly prevalent in automotive coatings, appliance exterior parts, packaging printing, and industrial protective applications due to their high aspect ratio and strong specular reflection capabilities. The metallic feel, brightness, and angle-dependent color variation of flake-shaped metallic pigments largely depend on the integrity of their flake structure and surface condition. However, existing flake-shaped metallic pigments still have certain shortcomings in practical applications. Taking aluminum flake pigments as an example, they are prone to surface reactions in aqueous systems, humid environments, or media containing corrosive components, leading to a decrease in metallic luster, color changes, and a deterioration in decorative effects. In severe cases, this can even affect storage stability and safety during use. Therefore, improving the water resistance and corrosion resistance of metallic pigments has always been a key focus in this field.
[0003] To address the aforementioned issues, existing technologies typically employ inorganic passivation, oxide coating, or organosilane coating to form a protective layer on the surface of metallic pigments. While these methods can improve resistance to erosion to some extent, they mostly involve coating the entire surface of the flake-like particles. This full-surface treatment approach often requires forming a relatively continuous or even thick film, which can easily affect the specular reflection properties of large areas of the flake-like metallic pigment, resulting in reduced metallic appearance, decreased brightness, or a dull appearance. Furthermore, existing technologies often fail to adequately distinguish the differences in structural characteristics and failure behavior between the edge areas and the large areas of the flake-like metallic substrate, thus making it difficult to balance protective performance with the preservation of optical properties.
[0004] Therefore, there is an urgent need to provide a new metallic pigment and its preparation method, so as to improve water resistance and corrosion resistance while maintaining the original metallic luster and decorative effect of the flake metallic pigment as much as possible. Summary of the Invention
[0005] To overcome the shortcomings of existing technologies, the present invention aims to provide a metallic pigment for metal watchbands and its preparation process. The metallic pigment comprises a flake-like metal substrate and a composite film layer formed on its surface. The composite film layer includes a composite protective ring layer located at the edge region of the flake-like metal substrate and an ultrathin regulating layer located in the large surface area. The composite protective ring layer is formed by in-situ composite of metal conversion bonding units and organosilicon network units. The preparation method includes pretreatment, differential activation, restricted hydrolysis deposition, and staged curing. This approach, by focusing on protecting the edge region and controlling the lightweighting of the large surface area, can improve water resistance, corrosion resistance, and interface stability while reducing the adverse effects on the large surface reflectivity of the flake-like metal substrate, thus helping to maintain metallic luster, brightness, and decorative effect.
[0006] To achieve the above objectives, the present invention provides the following technical solution: A metallic pigment for metal watch straps includes a sheet-like metal substrate and a composite film layer formed on the surface of the sheet-like metal substrate. The composite film layer includes a composite protective ring layer located in the edge region of the sheet-like metal substrate and an ultra-thin adjustment layer located in the large surface region of the sheet-like metal substrate. The edge region is a strip-shaped region extending inward from the outer edge of the sheet-like metal substrate by 0.1-2 μm; The composite protective ring layer is formed by in-situ composite of metal conversion bonding units and organosilicon network units. The thickness of the composite protective ring layer is 15-120 nm, the thickness of the ultrathin adjustment layer is 1-15 nm, and the thickness of the composite protective ring layer is 2-10 times the thickness of the ultrathin adjustment layer.
[0007] Preferably, the sheet-like metal substrate is one or more of the following: sheet-like aluminum pigment, sheet-like aluminum-magnesium alloy pigment, vacuum-deposited aluminum sheet, sheet-like copper-zinc alloy pigment, and sheet-like stainless steel pigment.
[0008] Preferably, the median particle size of the sheet-like metal matrix is 8-30 μm, the thickness is 0.03-0.25 μm, and the aspect ratio is 50-300.
[0009] Preferably, the metal conversion bonding unit includes at least one of zirconium-based conversion structure and titanium-based conversion structure, wherein the zirconium-based conversion structure and the titanium-based conversion structure include at least one bonding structure selected from Al-O-Zr, Al-O-Ti, Zr-O-Zr, and Ti-O-Ti.
[0010] Preferably, the organosilicon network unit is formed by the condensation of hydrolyzable organosilicon alkyl groups, including a Si-O-Si network structure and at least one functional group selected from alkyl, epoxy, and amino groups connected to the Si-O-Si network structure.
[0011] Preferably, the composite protective ring layer is continuously distributed along the outer edge of the sheet-like metal substrate and gradually decreases from the outer edge to the large surface area to form a thickness gradient structure.
[0012] A process for preparing a metallic pigment for metal watchbands, comprising the following steps: S1. Pre-treat the sheet metal substrate to remove residual grinding aids, fatty acids, waxes and low-molecular-weight organic matter from its surface; S2. The pretreated sheet metal substrate is dispersed in an aqueous alcohol system for differential activation, so that the surface reactivity of the edge region of the sheet metal substrate is higher than that of the large surface region. S3. Add a composite precursor liquid containing a metal precursor and an organosilane precursor to a differentially activated dispersion system. Under restricted hydrolysis deposition conditions, the metal precursor and the organosilane precursor are preferentially deposited in the edge region and composited in situ to form a composite protective ring layer, while an ultrathin conditioning layer is formed in the large area. S4. The product obtained in step S3 is cured to obtain the metallic pigment.
[0013] Preferably, in step S1, the pretreatment uses at least one of ethyl acetate, isopropanol, n-heptane, and isoalkanes as the washing medium, the pretreatment temperature is 20-40℃, and the pretreatment time is 10-60 min. In step S2, the volume fraction of water in the aqueous alcohol system is 2-12%, the pH of the system is 3.5-5.5, the treatment temperature is 20-40℃, and the treatment time is 10-40 min.
[0014] Preferably, in step S3, the metal precursor is at least one of zirconium salt precursor and titanium salt precursor; the organosilane precursor is at least one of methyltrialkoxysilane, γ-glycidoxypropyltrialkoxysilane, and γ-aminopropyltrialkoxysilane. The composite precursor liquid is added dropwise to the differentially activated dispersion system, and the system is controlled to be in a slightly undersaturated or low supersaturated state.
[0015] Preferably, step S4 employs a phased curing process, including pre-curing at 60-90℃ for 20-90 minutes and then final curing at 90-120℃ for 30-180 minutes.
[0016] Compared with the prior art, the beneficial effects of the present invention are as follows: 1. This invention achieves differentiated functional allocation between the edge and large-area regions of a sheet-like metal substrate by constructing a composite protective ring layer at the edge and an ultra-thin regulating layer in the large-area region. Since the edge region of a sheet-like metal substrate typically has higher surface activity and is more prone to media intrusion and failure initiation, this invention utilizes a continuous composite protective ring layer formed in situ by combining metal conversion bonding units and organosilicon network units in this region. This allows for the creation of a more stable interface bonding and barrier structure at the edge, effectively improving the barrier capability against moisture, oxygen, and corrosive media, and enhancing the water resistance, corrosion resistance, and interface stability of the metallic pigment. Simultaneously, the formation of only an ultra-thin regulating layer in the large-area region minimizes the adverse effects of the film layer on the specular reflection performance of the sheet-like metal substrate while ensuring surface regulation, thus maintaining its original metallic luster, brightness, and decorative effect. Furthermore, the composite protective ring layer is continuously distributed along the outer edge and gradually decreases towards the large-area region, forming a thickness gradient structure. This helps to mitigate the abrupt interface change between the edge and large-area regions, reducing the possibility of local stress concentration and defects in the film layer, further improving the film bonding strength and structural stability. Accordingly, through a preparation process that combines pretreatment, differential activation, restricted hydrolysis deposition, and staged curing, the composite film can be preferentially oriented and stably formed in the edge region, thus giving the present invention a more prominent comprehensive technical advantage in maintaining both protective and optical properties. Attached Figure Description
[0017] Figure 1 This is a flowchart illustrating the preparation process of the metallic pigment for metal watch straps according to the present invention. Figure 2 This is a SEM image of the metallic pigment prepared in Example 1 of the present invention. Detailed Implementation
[0018] The present invention will now be clearly and completely described in conjunction with embodiments thereof. Obviously, the described embodiments are merely some, not all, of the embodiments of the present invention. All other embodiments obtained by those skilled in the art based on the embodiments of the present invention without creative effort are within the scope of protection of the present invention.
[0019] Please see Figure 1-2 The present invention provides a technical solution: Example 1 This embodiment provides a metallic pigment for metal watchbands, prepared using flake-shaped aluminum pigment as the flake-shaped metal matrix. The main raw materials used are as follows: the flake-shaped aluminum pigment was purchased from ECKART GmbH, Germany, and pre-tested showed a median particle size of approximately 14.8 μm, a thickness of approximately 0.08 μm, and an aspect ratio of approximately 185; ethyl acetate, isopropanol, anhydrous ethanol, n-heptane, and glacial acetic acid were all purchased from Sinopharm Chemical Reagent Co., Ltd., and were of analytical grade; zirconium oxychloride octahydrate, methyltrimethoxysilane, and γ-glycidoxypropyltrimethoxysilane were all purchased from Aladdin Reagent (Shanghai) Co., Ltd., wherein the purity of methyltrimethoxysilane was not less than 98%, and the purity of γ-glycidoxypropyltrimethoxysilane was not less than 98%.
[0020] This embodiment also provides a method for preparing metallic pigments for metal watch straps, specifically including the following steps: S1. Weigh 100.0g of flake aluminum pigment and place it in a 2L three-necked glass flask. Add 400mL of ethyl acetate and 200mL of isopropanol. Mechanically stir at 300rpm for 30min at 25℃ to remove residual grinding aids, fatty acids, waxes, and low-molecular-weight organic matter from the surface of the flake aluminum pigment. After stirring, filter the mixture using a polytetrafluoroethylene (PTFE) membrane and rinse the filter cake once with 100mL of isopropanol. Then, transfer the filter cake to a vacuum drying oven and vacuum dry it at 40℃ for 30min to obtain the pretreated flake aluminum pigment. Organic residues on the surface of the flake aluminum pigment can shield highly active sites at the edges and weaken the preferential adsorption and deposition of subsequent precursors in the edge region. Gentle washing to remove surface residues helps to unify the initial state of the substrate surface, thereby improving the reproducibility of subsequent differential activation and selective film formation.
[0021] S2. Add 100.0g of pretreated flake aluminum pigment to a 2L three-necked glass flask equipped with a mechanical stirrer, thermometer, and constant-pressure dropping funnel. Add 920mL of anhydrous ethanol and 80mL of deionized water, maintaining the system temperature at 30℃ and the stirring speed at 250rpm. Then, slowly add 2.3mL of glacial acetic acid to the system to adjust the pH to 4.4, and continue stirring for 20min to allow mild activation of the edge region of the flake aluminum pigment. During this process, the bridging oxygen bonds in the oxide film on the surface of the flake aluminum pigment undergo hydroxylation in the presence of trace amounts of water. The specific reaction process is shown below: ≡Al-O-Al≡ + H2O → 2≡Al-OH; Because the edge regions of the flake-like particles have higher curvature, higher defect density, and less complete surface oxide film structure, their degree of hydroxylation and surface reactivity are higher than those of the larger surface regions, thus creating conditions for preferential deposition of subsequent composite precursors in the edge regions. The activation conditions used are mild acidic conditions, the purpose of which is to amplify the difference in reactivity between the edge regions and the larger surface regions of the flake-like aluminum pigment, rather than to subject the substrate to significant corrosion or etching.
[0022] S3. Confined hydrolysis sedimentation S301. Preparation of metal precursor solution A: Weigh 0.80 g zirconium oxychloride octahydrate, add it to 20 mL of deionized water and 60 mL of anhydrous ethanol, and stir magnetically for 15 min at room temperature until a clear and transparent solution is formed. S302. Preparation of organosilane precursor solution B: Weigh 1.20 g methyltrimethoxysilane and 0.80 g γ-glycidoxypropyltrimethoxysilane, add them to 120 mL anhydrous ethanol, then add 6.0 mL deionized water and 0.60 mL glacial acetic acid, and stir at 25 °C for 30 min for pre-hydrolysis; during the pre-hydrolysis process, the organosilane can be hydrolyzed by the following reaction: R-Si(OCH3)3+ 3H2O → R-Si(OH)3+ 3CH3OH; R represents methyl and γ-glycidoxypropyl, respectively. Solution A was then slowly added to solution B, and the mixture was stirred for another 10 minutes to obtain a total volume of approximately 208 mL of the composite precursor solution.
[0023] S303. Under the conditions of maintaining the differential activation system temperature at 30℃ and the stirring speed at 250 rpm, the above composite precursor solution was added dropwise to the differentially activated flake aluminum pigment dispersion system through a constant pressure dropping funnel. The dropping rate was controlled at 1.2 mL / min, and the total dropping time was approximately 173 min. Throughout the dropping process, the pH of the system was maintained between 4.3 and 4.8; when the pH exceeded 4.8, 0.10 mL of glacial acetic acid / 10 mL of ethanol mixture was added for fine-tuning. Using dropwise addition and controlling the system to a slightly undersaturated or slightly supersaturated state can inhibit the free nucleation and aggregation of precursors in the liquid phase, allowing metal precursors and organosilane precursors to preferentially migrate to the highly active sites at the edges and undergo heterogeneous deposition. The interfacial reaction can be illustrated as follows: ≡Al-OH + Zr(OH)4→ ≡Al-O-Zr(OH)3+ H2O; ≡Al-OH + R-Si(OH)3→ ≡Al-O-Si(OH)2R + H2O; ≡Zr-OH + HO-SiR(OH)2→ ≡Zr-O-SiR(OH)2+ H2O; 2R-Si(OH)3→ R-Si-O-Si-R + 3H2O; Zirconium-based species preferentially condense with hydroxyl groups on the aluminum surface to form an Al-O-Zr interfacial bond structure. The pre-hydrolyzed organosilanes further condense with hydroxyl groups on the aluminum surface, zirconium-based hydroxyl groups, and adjacent silanol groups, gradually forming organosilicon network units containing Si-O-Si and Zr-O-Si bonds, thus forming a composite protective ring layer in situ at the edge region. Due to the higher surface reactivity and stronger adsorption driving force at the edge region, the composite film layer preferentially thickens at the edge region, while only a thinner regulating layer is formed in the larger area. After the composite precursor liquid is added dropwise, the mixture is kept at 30℃ and stirred for 60 min to promote further condensation and fixation of the composite film layer at the edge region. Subsequently, the system is heated to 40℃ and the reaction continues for 30 min to improve the continuity and integrity of the primary film layer. After the reaction, the product is separated by filtration and washed once each with 150 mL of anhydrous ethanol and 100 mL of n-heptane to remove unreacted precursors and free oligomers, yielding a wet intermediate product.
[0024] S4. The above-mentioned wet intermediate product is placed in a vacuum drying oven and pre-cured at 75°C for 60 min to remove residual solvent and promote the stable adhesion of the nascent composite film to the surface of the flake aluminum pigment; then it is transferred to a nitrogen-protected oven and finally cured at 105°C for 120 min to further condense and densify the zirconium-based conversion structure and the organosilicon network unit, finally obtaining the metallic pigment. The technical principle of staged curing is that the pre-curing stage mainly completes the solvent removal and gentle fixation of the nascent film, avoiding the film from flowing, migrating or locally agglomerating before it is stable; the final curing stage further promotes the deep condensation between active groups such as Si-OH and Zr-OH, enhancing the density, interfacial bonding strength and structural stability of the composite protective ring layer.
[0025] Example 2 This embodiment provides a metallic pigment for metal watchbands, prepared using flake-shaped aluminum-magnesium alloy pigment as the flake-shaped metal matrix. The main raw materials used are as follows: the flake-shaped aluminum-magnesium alloy pigment was purchased from ECKART GmbH, Germany, and its median particle size was pre-tested to be approximately 16.2 μm, thickness approximately 0.10 μm, and aspect ratio approximately 162; ethyl acetate, isopropanol, anhydrous ethanol, n-heptane, and glacial acetic acid were all purchased from Sinopharm Chemical Reagent Co., Ltd., and were of analytical grade; tetraisopropyl titanate was purchased from Aladdin Reagent (Shanghai) Co., Ltd., with a purity of not less than 98%; methyltrimethoxysilane and γ-glycidoxypropyltrimethoxysilane were both purchased from Aladdin Reagent (Shanghai) Co., Ltd., and their purities were both not less than 98%.
[0026] This embodiment also provides a method for preparing metallic pigments for metal watch straps, specifically including the following steps: S1. Weigh 100.0g of flake aluminum-magnesium alloy pigment and place it in a 2L three-necked glass flask. Add 350mL of ethyl acetate and 250mL of isopropanol, and mechanically stir at 280rpm for 35min at 25℃. After stirring, filter the mixture using a polytetrafluoroethylene (PTFE) filter membrane and rinse the filter cake once with 120mL of isopropanol. Then, transfer the filter cake to a vacuum drying oven and vacuum dry it at 38℃ for 40min to obtain the pretreated flake aluminum-magnesium alloy pigment.
[0027] S2. Add 100.0g of pretreated flake aluminum-magnesium alloy pigment to a 2L three-necked glass flask equipped with a mechanical stirrer, thermometer, and constant-pressure dropping funnel. Add 900mL of anhydrous ethanol and 100mL of deionized water, maintaining the system temperature at 28℃ and the stirring speed at 240rpm. Then, slowly add 2.6mL of glacial acetic acid to the system to adjust the pH of the mixture to 4.2, and continue stirring for 25min to allow for gentle activation of the edge regions of the flake aluminum-magnesium alloy pigment.
[0028] S3. Confined hydrolysis sedimentation S301. Preparation of metal precursor solution A: Weigh 1.10 g tetraisopropyl titanate and add it to 80 mL of anhydrous ethanol. Stir magnetically for 10 min at room temperature. Then add 8.0 mL of isopropanol and 1.5 mL of deionized water and continue stirring for 10 min to obtain metal precursor solution A.
[0029] S302. Preparation of organosilane precursor solution B: Weigh 1.00 g methyltrimethoxysilane and 1.20 g γ-glycidyl etheroxypropyltrimethoxysilane, add them to 130 mL anhydrous ethanol, then add 7.0 mL deionized water and 0.70 mL glacial acetic acid, and stir at 25 °C for 35 min for pre-hydrolysis. Then slowly add solution A to solution B, mix, and continue stirring for 10 min to obtain a total volume of approximately 228 mL of composite precursor solution.
[0030] S303. Under the conditions of maintaining the differential activation system temperature at 28℃ and the stirring speed at 240 rpm, the above composite precursor solution was added dropwise to the differentially activated flake aluminum-magnesium alloy pigment dispersion system through a constant pressure dropping funnel. The dropping rate was controlled at 1.1 mL / min, and the total dropping time was approximately 207 min. Throughout the dropping process, the pH of the system was maintained between 4.1 and 4.6; when the pH exceeded 4.6, 0.10 mL of glacial acetic acid / 10 mL of ethanol mixture was added for fine-tuning. After the composite precursor solution was added, the system was kept at 28℃ and stirred for another 50 min; then the system was heated to 38℃ and the reaction continued for another 40 min. After the reaction was completed, the product was separated by vacuum filtration and washed once each with 150 mL of anhydrous ethanol and 120 mL of n-heptane to obtain a wet intermediate product.
[0031] S4. Place the above wet intermediate product in a vacuum drying oven and pre-cur it at 70°C for 70 min; then transfer it to a nitrogen-protected oven and finally cure it at 100°C for 150 min to obtain the metallic pigment.
[0032] Example 3 This embodiment provides a metallic pigment for metal watchbands, prepared using vacuum-deposited aluminum sheets as the sheet-like metal substrate. The main raw materials used are as follows: the vacuum-deposited aluminum sheets were purchased from Schlenk GmbH, Germany, with a pre-tested median particle size of approximately 11.5 μm, a thickness of approximately 0.04 μm, and an aspect ratio of approximately 288; ethyl acetate, isopropanol, anhydrous ethanol, n-heptane, and glacial acetic acid were all purchased from Sinopharm Chemical Reagent Co., Ltd., and were of analytical grade; zirconium oxychloride octahydrate was purchased from Aladdin Reagent (Shanghai) Co., Ltd., and was of analytical grade; methyltrimethoxysilane and γ-aminopropyltriethoxysilane were purchased from Aladdin Reagent (Shanghai) Co., Ltd., and both had a purity of not less than 98%.
[0033] This embodiment also provides a metallic pigment for metal watch straps, specifically including the following steps: S1. Weigh 100.0g of vacuum-deposited aluminum sheet and place it in a 2L three-necked glass flask. Add 300mL of ethyl acetate and 250mL of isopropanol, and mechanically stir at 260rpm for 25min at 22℃. After stirring, filter the mixture using a polytetrafluoroethylene (PTFE) filter membrane and rinse the filter cake once with 100mL of isopropanol. Then, transfer the filter cake to a vacuum drying oven and vacuum dry it at 35℃ for 25min to obtain the pretreated vacuum-deposited aluminum sheet.
[0034] S2. Add 100.0g of pretreated vacuum-deposited aluminum sheet to a 2L three-necked glass flask equipped with a mechanical stirrer, thermometer, and constant-pressure dropping funnel. Add 950mL of anhydrous ethanol and 50mL of deionized water, maintaining the system temperature at 26℃ and the stirring speed at 220rpm. Then, slowly add 1.8mL of glacial acetic acid to the system to adjust the pH of the mixture to 4.8, and continue stirring for 15min to allow for gentle activation of the edge region of the vacuum-deposited aluminum sheet.
[0035] S3. Confined hydrolysis sedimentation S301. Preparation of metal precursor solution A: Weigh 0.65 g of zirconium oxychloride octahydrate, add it to 15 mL of deionized water and 55 mL of anhydrous ethanol, and stir magnetically for 15 min at room temperature until a clear and transparent solution is formed. S302. Preparation of organosilane precursor solution B: Weigh 1.40 g of methyltrimethoxysilane and 0.60 g of γ-aminopropyltriethoxysilane, add them to 125 mL of anhydrous ethanol, then add 5.0 mL of deionized water and 0.50 mL of glacial acetic acid, and stir for pre-hydrolysis at 25 °C for 25 min. Then slowly add solution A to solution B, mix, and continue stirring for 10 min to obtain a total of approximately 200 mL of composite precursor solution. S303. Under the conditions of maintaining the differential activation system temperature at 26℃ and the stirring speed at 220 rpm, the above composite precursor solution was added dropwise to the differentially activated vacuum-deposited aluminum sheet dispersion system through a constant pressure dropping funnel. The dropping rate was controlled at 1.0 mL / min, and the total dropping time was approximately 200 min. Throughout the dropping process, the pH of the system was maintained between 4.6 and 5.0; when the pH exceeded 5.0, 0.10 mL of glacial acetic acid / 10 mL of ethanol mixture was added for fine-tuning. After the composite precursor solution was added, the system was kept at 26℃ and stirred for another 45 min; subsequently, the system was heated to 35℃ and the reaction continued for another 25 min. After the reaction was completed, the product was separated by vacuum filtration and washed once each with 120 mL of anhydrous ethanol and 100 mL of n-heptane to obtain a wet intermediate product.
[0036] S4. Place the above wet intermediate product in a vacuum drying oven and pre-cur it at 65°C for 50 min; then transfer it to a nitrogen-protected oven and finally cure it at 95°C for 100 min to obtain the metallic pigment.
[0037] Example 4 This embodiment provides a metallic pigment for metal watchbands, prepared using flake-shaped aluminum pigment as the flake-shaped metal matrix. The main raw materials used are as follows: the flake-shaped aluminum pigment was purchased from ECKART GmbH, Germany, and its median particle size was pre-tested to be approximately 22.4 μm, thickness approximately 0.12 μm, and aspect ratio approximately 187; ethyl acetate, isopropanol, anhydrous ethanol, n-heptane, and glacial acetic acid were all purchased from Sinopharm Chemical Reagent Co., Ltd., and were of analytical grade; zirconium oxychloride octahydrate and tetraisopropyl titanate were both purchased from Aladdin Reagent (Shanghai) Co., Ltd., with tetraisopropyl titanate having a purity of not less than 98%; methyltrimethoxysilane, γ-glycidoxypropyltrimethoxysilane, and γ-aminopropyltriethoxysilane were all purchased from Aladdin Reagent (Shanghai) Co., Ltd., and their purity was not less than 98%.
[0038] This embodiment also provides a method for preparing metallic pigments for metal watch straps, specifically including the following steps: S1. Weigh 100.0g of flake aluminum pigment and place it in a 2L three-necked glass flask. Add 450mL of ethyl acetate and 180mL of isopropanol, and mechanically stir at 320rpm for 40min at 25℃. After stirring, filter the mixture through a polytetrafluoroethylene (PTFE) membrane and rinse the filter cake once with 120mL of isopropanol. Then, transfer the filter cake to a vacuum drying oven and vacuum dry it at 42℃ for 35min to obtain the pretreated flake aluminum pigment.
[0039] S2. Add 100.0g of pretreated flake aluminum pigment to a 2L three-necked glass flask equipped with a mechanical stirrer, thermometer, and constant-pressure dropping funnel. Add 880mL of anhydrous ethanol and 120mL of deionized water, maintaining the system temperature at 32℃ and the stirring speed at 260rpm. Then, slowly add 2.8mL of glacial acetic acid to the system to adjust the pH of the mixture to 4.0, and continue stirring for 30min to gently activate the edge areas of the flake aluminum pigment.
[0040] S3. Confined hydrolysis sedimentation S301. Preparation of metal precursor solution A: Weigh 0.45 g zirconium oxychloride octahydrate and 0.55 g tetraisopropyl titanate. First, add zirconium oxychloride octahydrate to 15 mL of deionized water and 45 mL of anhydrous ethanol and stir for 15 min. Then, dissolve tetraisopropyl titanate in 20 mL of anhydrous ethanol and 6.0 mL of isopropanol. Mix the two portions and continue stirring for 10 min to obtain metal precursor solution A. S302. Preparation of organosilane precursor solution B: Weigh 0.90 g methyltrimethoxysilane, 0.70 g γ-glycidoxypropyltrimethoxysilane, and 0.50 g γ-aminopropyltriethoxysilane. Add them to 140 mL of anhydrous ethanol, then add 8.0 mL of deionized water and 0.80 mL of glacial acetic acid. Stir and pre-hydrolyze at 25 °C for 40 min. Solution A was then slowly added to solution B, and after mixing, the mixture was stirred for another 15 minutes to obtain a total volume of approximately 235 mL of the composite precursor solution.
[0041] S303. Under the conditions of maintaining the differential activation system temperature at 32℃ and the stirring speed at 260 rpm, the above composite precursor solution was added dropwise to the differentially activated flake aluminum pigment dispersion system through a constant pressure dropping funnel. The dropping rate was controlled at 1.3 mL / min, and the total dropping time was approximately 181 min. Throughout the dropping process, the pH of the system was maintained between 3.9 and 4.5; when the pH exceeded 4.5, 0.10 mL of glacial acetic acid / 10 mL of ethanol mixture was added for fine-tuning. After the composite precursor solution was added, the system was kept at 32℃ and stirred for another 70 min; then the system was heated to 42℃ and the reaction continued for another 35 min. After the reaction was completed, the product was separated by vacuum filtration and washed once each with 180 mL of anhydrous ethanol and 120 mL of n-heptane to obtain a wet intermediate product.
[0042] S4. Place the above wet intermediate product in a vacuum drying oven and pre-cur it at 80°C for 80 min; then transfer it to a nitrogen-protected oven and finally cure it at 110°C for 150 min to obtain the metallic pigment.
[0043] Comparative Example Comparative Example 1 This comparative example provides a metallic pigment without composite film construction treatment, using flake aluminum pigment as the flake metal matrix. The main raw materials used are as follows: the flake aluminum pigment was purchased from ECKART GmbH, Germany, and its median particle size was approximately 14.8 μm, thickness was approximately 0.08 μm, and aspect ratio was approximately 185, according to preliminary testing; ethyl acetate and isopropanol were purchased from Sinopharm Chemical Reagent Co., Ltd., and were of analytical grade.
[0044] This comparative example also provides a method for processing metallic pigments, specifically including the following steps: S1. Weigh 100.0g of flake aluminum pigment and place it in a 2L three-necked glass flask. Add 400mL of ethyl acetate and 200mL of isopropanol. Stir mechanically at 300rpm for 30min at 25℃ to remove residual grinding aids, fatty acids, waxes and low molecular weight organic matter on the surface of the flake aluminum pigment.
[0045] S2. After stirring, the mixture was filtered through a polytetrafluoroethylene filter membrane and rinsed once with 100 mL of isopropanol. The filter cake was then transferred to a vacuum drying oven and dried under vacuum at 40 °C for 30 min to obtain the metallic pigment sample of Comparative Example 1.
[0046] Comparative Example 1 was not subjected to differential activation treatment, nor was it subjected to composite precursor deposition and curing treatment. The resulting sample served as a blank control sample without composite film construction.
[0047] Comparative Example 2 This comparative example provides a fully surface-coated metallic pigment prepared using flake-shaped aluminum pigment as the flake-shaped metal matrix. The main raw materials used are as follows: the flake-shaped aluminum pigment was purchased from ECKART GmbH, Germany, with a pre-tested median particle size of approximately 14.8 μm, a thickness of approximately 0.08 μm, and an aspect ratio of approximately 185; ethyl acetate, isopropanol, anhydrous ethanol, n-heptane, and glacial acetic acid were all purchased from Sinopharm Chemical Reagent Co., Ltd., and were of analytical grade; zirconium oxychloride octahydrate, methyltrimethoxysilane, and γ-glycidoxypropyltrimethoxysilane were all purchased from Aladdin Reagent (Shanghai) Co., Ltd., with methyltrimethoxysilane having a purity of not less than 98%, and γ-glycidoxypropyltrimethoxysilane having a purity of not less than 98%.
[0048] This comparative example also provides a method for preparing a fully surface-coated metallic pigment, specifically including the following steps: S1. Weigh 100.0g of flake aluminum pigment and place it in a 2L three-necked glass flask. Add 400mL of ethyl acetate and 200mL of isopropanol, and mechanically stir at 300rpm for 30min at 25℃. After stirring, filter the mixture through a polytetrafluoroethylene (PTFE) membrane and rinse the filter cake once with 100mL of isopropanol. Then, transfer the filter cake to a vacuum drying oven and vacuum dry it at 40℃ for 30min to obtain the pretreated flake aluminum pigment.
[0049] S2. Add 100.0g of pretreated flake aluminum pigment to a 2L three-necked glass flask equipped with a mechanical stirrer, thermometer, and feeding funnel. Add 920mL of anhydrous ethanol and 80mL of deionized water, maintaining the system temperature at 30℃ and the stirring speed at 250rpm. Then add 2.3mL of glacial acetic acid to the system to adjust the pH of the mixture to 4.4, and continue stirring for 10min. No differential activation holding process is included in this step.
[0050] S3. Conventional monolithic encapsulated sediments S301. Preparation of metal precursor solution A: Weigh 0.80 g of zirconium oxychloride octahydrate, add it to 20 mL of deionized water and 60 mL of anhydrous ethanol, and stir magnetically for 15 min at room temperature until a clear and transparent solution is formed. S302. Preparation of organosilane precursor solution B: Weigh 1.20 g of methyltrimethoxysilane and 0.80 g of γ-glycidyl etheroxypropyltrimethoxysilane, add them to 120 mL of anhydrous ethanol, then add 6.0 mL of deionized water and 0.60 mL of glacial acetic acid, and stir for pre-hydrolysis at 25 °C for 30 min. Then slowly add solution A to solution B, mix, and continue stirring for 10 min to obtain a total of approximately 208 mL of composite precursor solution. S303. Under the conditions of maintaining the system temperature at 30 °C and the stirring speed at 250 rpm, add the above composite precursor solution to the flake aluminum pigment dispersion system in one go, and continue stirring for 120 min. Throughout the reaction, the pH of the system was controlled between 4.3 and 4.8; when the pH exceeded 4.8, 0.10 mL of a mixture of glacial acetic acid and 10 mL of ethanol was added for fine-tuning. After the reaction was completed, the system was heated to 40 °C and the reaction was continued for 30 min. Subsequently, the product was separated by vacuum filtration and washed once each with 150 mL of anhydrous ethanol and 100 mL of n-heptane to obtain the wet intermediate product.
[0051] S4. The above wet intermediate product was placed in a vacuum drying oven and pre-cured at 75°C for 60 min; then it was transferred to a nitrogen-protected oven and finally cured at 105°C for 120 min to obtain the full-surface coated metallic pigment sample of Comparative Example 2.
[0052] Comparative Example 2 used the same type of metal precursor and organosilane precursor as Example 1, but did not perform edge region differential activation, and the composite precursor solution was added in a one-time conventional deposition process. Therefore, the resulting film was mainly distributed on the surface of the flake aluminum pigment in an overall coating manner.
[0053] Performance testing To verify the surface structure characteristics of the metallic pigment prepared according to this invention, the sample obtained in Example 1 was used to observe the surface morphology of the metallic pigment using a scanning electron microscope. The results are as follows: Figure 2 As shown, the obtained metallic pigment maintains a complete flake-like morphology overall, with relatively flat large-area areas of the particles, and no obvious granular deposition or severe agglomeration is observed. With increasing magnification, continuous and uniform reinforcing bands can be observed forming at the particle edges, while no significant thick coating appears in the large-area areas, indicating that the composite film is preferentially constructed mainly at the edges of the flake-like metal substrate. This morphology demonstrates that the present invention effectively maintains the integrity of the large-area of the flake-like metal substrate while strengthening edge protection, which is beneficial for balancing media resistance and metallic luster.
[0054] To verify the structural characteristics and performance advantages of the metallic pigment prepared by this invention, the samples obtained in the examples and comparative examples were tested as follows. First, the intrinsic stability of the powder was tested. Specifically, 0.500 g of each sample was weighed and placed in a 100 mL stoppered conical flask, 20.0 mL of deionized water was added, and the samples were kept at a constant temperature of 40±1℃ for 168 h. The cumulative gas evolution per unit mass of pigment was determined by the liquid displacement and gas collection method. Each group of samples was tested in parallel three times, and the average value was taken as the final test result. Second, the film structure of the samples was characterized. Specifically, TEM cross-sectional samples were prepared from the powder samples, and the film layer in the edge region and large area of a single sheet-like particle was observed. The thickness of the edge film layer and the thickness of the large area film layer were statistically analyzed for 20 randomly selected particles. At the same time, EDS line scan tests were combined to compare the signal intensity of Si, Zr, or Ti elements in the edge region and the large area to characterize the distribution characteristics of the composite film layer on the surface of the sheet-like metal substrate.
[0055] To evaluate the resistance of the metallic pigments prepared in this invention to various media in the coating state, each sample was added to a transparent acrylic varnish at a mass fraction of 10 wt%. After dispersion at low speed for 15 min, the mixture was sprayed onto the surface of a tinplate, with the dry film thickness controlled at 20 ± 3 μm. The samples were allowed to stand at room temperature for 24 h, and then dried at 80℃ for 30 min to obtain the test coating. The obtained coating was then tested for water resistance, damp heat stability, and neutral salt spray performance. The water resistance test was performed according to GB / T1733-1993 "Determination of Water Resistance of Paint Films", the damp heat stability test was performed according to GB / T 1740-2007 "Determination of Damp Heat Resistance of Paint Films", and the neutral salt spray performance test was performed according to GB / T 1771-2007 "Determination of Neutral Salt Spray Resistance of Paints and Varnishes".
[0056] To evaluate the retention of metallic decorative effects before and after sample treatment, the appearance retention performance of each coating sample was also tested. A multi-angle colorimeter was used to measure the lightness change of the samples, and the lightness L* retention rate under fixed geometric conditions was used as the evaluation index of appearance retention ability to characterize the retention of metallic luster and decorative effects of the metallic pigment prepared in this invention after being treated by a medium. The relevant test results are shown in Tables 1 and 2: Table 1. Structural characterization results of Examples 1-4 and Comparative Examples 1-2 Note: *Edge element enrichment factor refers to the average ratio of the combined signal intensity of Si and Zr / Ti in the edge region to that in the large area region during EDS line scan.
[0057] Table 2. Performance test data of Examples 1-4 and Comparative Examples 1-2 Note: Surface change levels are recorded from 0 to 5, where 0 indicates no visible abnormalities, 1 indicates slight loss of gloss or very few pinholes, 2 indicates slight discoloration / slight blistering, 3 indicates significant loss of gloss with localized blistering, 4 indicates significant blistering or corrosion spots, and 5 indicates severe loss of gloss, blistering, corrosion with coating damage.
[0058] As shown in Table 1, Examples 1-4 all exhibit a clear "thick at the edges, thin on the large surface" film distribution characteristic, with the edge / large surface thickness ratio all exceeding 6 times, while Comparative Example 2 is only 1.3, indicating that it is closer to a uniform overall coating; Comparative Example 1 has virtually no identifiable continuous film layer. This demonstrates that the present invention, through differential activation and drop-by-drop confined deposition, enables the metal precursor and organosilane precursor to preferentially undergo heterogeneous deposition at highly active sites at the edges, thus constructing a relatively thicker composite protective ring layer in the edge region, while retaining only an ultrathin adjustment layer in the large surface region. Example 4 has the thickest edge film layer and the highest edge element enrichment factor, indicating that the bimetallic precursor system has a stronger composite deposition capability in the edge region; Example 3 has the thinnest edge film layer, but its large surface film layer is also the thinnest, thus having an advantage in maintaining the integrity of the large surface of the sheet-like substrate.
[0059] Table 2 further shows that the embodiments of the present invention are significantly superior to the two comparative examples in terms of gas evolution, water resistance, damp heat stability, and salt spray corrosion inhibition. Comparative Example 1 did not form a protective film layer, allowing water, oxygen, and corrosive ions to directly enter the aluminum substrate surface from the edges and defect sites of the flaky particles. Therefore, it had the highest gas evolution, the worst water resistance and damp heat resistance, and the widest salt spray spread. Although Comparative Example 2 used the same type of precursor as Example 1, the lack of edge differential activation and the one-time addition of the composite precursor liquid made free nucleation and overall deposition more likely to occur in the liquid phase. This resulted in a film layer that tended to be distributed uniformly on the particle surface, with insufficient protection in the edge areas and a significantly thicker film layer in large areas. While this structure provided some protection compared to the blank sample, its blocking efficiency at key edge sites was still lower than that of the embodiments of the present invention. Therefore, its gas evolution, media resistance, and salt spray results were significantly inferior to Examples 1 and 4.
[0060] Among the various embodiments, Example 1 exhibits the most balanced overall performance. This is because the zirconium-based conversion bonding unit and the organosilicon network unit form a relatively stable and continuous composite protective ring layer in the edge region. The edge film thickness is moderate, while the film thickness in the large area is controlled at a low level, thus balancing protective capability and metallic effect retention. Example 2 uses flake aluminum-magnesium alloy pigments and titanium-based precursors, and its overall stability is still good. However, due to differences in matrix composition and deposition kinetics, its edge film is relatively wider, and the large area layer is slightly thicker, so its brightness retention rate is slightly lower than that of Example 1. Example 3 uses vacuum-deposited aluminum sheets, which are thinner and have stronger specular reflection capabilities, thus achieving the highest brightness L* retention rate. However, due to the thinner matrix and more sensitive edges, its water resistance and salt spray performance are slightly weaker than those of Example 1. Example 4 has the lowest gas evolution and the best water and salt spray resistance because the zirconium / titanium dual precursors participate in the film formation and the edge protective ring layer is the thickest. However, because the edge film layer and the local large-area adjustment layer are relatively thicker, its optical retention capability is slightly lower than that of Example 1 and Example 3.
[0061] Although embodiments of the invention have been shown and described, it will be understood by those skilled in the art that various changes, modifications, substitutions and variations can be made to these embodiments without departing from the principles and spirit of the invention, the scope of which is defined by the appended claims and their equivalents.
Claims
1. A metallic pigment for use in metal watch straps, characterized in that, It includes a sheet-like metal substrate and a composite film layer formed on the surface of the sheet-like metal substrate. The composite film layer includes a composite protective ring layer located in the edge region of the sheet-like metal substrate and an ultrathin adjustment layer located in the large surface region of the sheet-like metal substrate. The edge region is a strip-shaped region extending inward from the outer edge of the sheet-like metal substrate by 0.1-2 μm; The composite protective ring layer is formed by in-situ composite of metal conversion bonding units and organosilicon network units. The thickness of the composite protective ring layer is 15-120 nm, the thickness of the ultrathin adjustment layer is 1-15 nm, and the thickness of the composite protective ring layer is 2-10 times the thickness of the ultrathin adjustment layer.
2. The metallic pigment for metal watch straps according to claim 1, characterized in that, The sheet-like metal substrate is one or more of the following: sheet-like aluminum pigment, sheet-like aluminum-magnesium alloy pigment, vacuum-deposited aluminum sheet, sheet-like copper-zinc alloy pigment, and sheet-like stainless steel pigment.
3. A metallic pigment for metal watch straps according to claim 2, characterized in that, The median particle size of the sheet-like metal matrix is 8-30 μm, the thickness is 0.03-0.25 μm, and the aspect ratio is 50-300.
4. The metallic pigment for metal watch straps according to claim 1, characterized in that, The metal conversion bonding unit includes at least one of zirconium-based conversion structure and titanium-based conversion structure, wherein the zirconium-based conversion structure and the titanium-based conversion structure include at least one bonding structure selected from Al-O-Zr, Al-O-Ti, Zr-O-Zr, and Ti-O-Ti.
5. A metallic pigment for metal watch straps according to claim 1, characterized in that, The organosilicon network unit is formed by the condensation of hydrolyzable organosilicon alkyl groups and includes a Si-O-Si network structure and at least one functional group selected from alkyl, epoxy, and amino groups connected to the Si-O-Si network structure.
6. A metallic pigment for metal watch straps according to claim 1, characterized in that, The composite protective ring layer is continuously distributed along the outer edge of the sheet-like metal substrate and gradually decreases from the outer edge to the large surface area to form a thickness gradient structure.
7. A process for preparing a metallic pigment for metal watch straps, used to prepare the metallic pigment according to any one of claims 1-6, characterized in that, Includes the following steps: S1. Pre-treat the sheet metal substrate to remove residual grinding aids, fatty acids, waxes and low-molecular-weight organic matter from its surface; S2. The pretreated sheet metal substrate is dispersed in an aqueous alcohol system for differential activation, so that the surface reactivity of the edge region of the sheet metal substrate is higher than that of the large surface region. S3. Add a composite precursor liquid containing a metal precursor and an organosilane precursor to a differentially activated dispersion system. Under restricted hydrolysis deposition conditions, the metal precursor and the organosilane precursor are preferentially deposited in the edge region and composited in situ to form a composite protective ring layer, while an ultrathin conditioning layer is formed in the large area. S4. The product obtained in step S3 is cured to obtain the metallic pigment.
8. The preparation process of a metallic pigment for metal watch straps according to claim 7, characterized in that, In step S1, the pretreatment uses at least one of ethyl acetate, isopropanol, n-heptane, and isoalkanes as the washing medium, the pretreatment temperature is 20-40℃, and the pretreatment time is 10-60 min. In step S2, the volume fraction of water in the aqueous alcohol system is 2-12%, the pH of the system is 3.5-5.5, the treatment temperature is 20-40℃, and the treatment time is 10-40 min.
9. The preparation process of a metallic pigment for metal watch straps according to claim 7, characterized in that, In step S3, the metal precursor is at least one of zirconium salt precursor and titanium salt precursor; the organosilane precursor is at least one of methyltrialkoxysilane, γ-glycidoxypropyltrialkoxysilane, and γ-aminopropyltrialkoxysilane. The composite precursor liquid is added dropwise to the differentially activated dispersion system, and the system is controlled to be in a slightly undersaturated or low supersaturated state.
10. The preparation process of a metallic pigment for a metal watchband according to claim 7, characterized in that, Step S4 employs a phased curing process, including pre-curing at 60-90℃ for 20-90 minutes and then final curing at 90-120℃ for 30-180 minutes.